Chaos in Freedom: Understanding Positive and Negative Freedom through Classroom Disorder and Montessori Education - Kalea Humayraa Nasution; Putu Ega Yudia Mastika (Global Education Journal, 2026)
Freedom is commonly associated with choice, agency, and personal growth, yet everyday classroom experience shows that freedom without structure can quickly become disorder. This study examines how freedom can be used responsibly in educational settings by interpreting a classroom incident of disruption through Isaiah Berlin’s distinction between positive and negative liberty and Maria Montessori’s principle of freedom within order. The study asks three questions: why freedom sometimes leads to disorder in group settings, how rules and guidance make freedom meaningful, and what educational insight can be drawn from Berlin and Montessori for managing freedom productively. Using a qualitative design, the study draws on classroom observation, a focused literature review, and Socratic interviews with five classmates. The findings indicate that unstructured freedom initially produced excitement but rapidly evolved into noise, confusion, and reduced mutual consideration. Interpreted through Berlin, the classroom displayed “freedom to” act without sufficient “freedom from” disruption. Interpreted through Montessori, the episode illustrates that choice becomes educationally valuable only within a prepared environment shaped by norms, routines, and responsibility. The study contributes a child-centered and theoretically grounded account of why rules do not necessarily limit freedom, but can instead make meaningful freedom possible in classroom life.